Peran Guru PAK Sebagai Fasilitator Dalam Pembelajaran - Cindy Hasibuan; Dorlan Naibaho (JOURNAL SAINS STUDENT RESEARCH, 2025)
Christian Religious Education (PAK) teachers have a strategic role as facilitators in forming students' characters based on Christian values. As facilitators, PAK teachers not only present material openly, but also create an interactive, reflective and contextual learning atmosphere, so that students can understand and apply the teachings of the Christian faith in their daily lives. This research aims to analyze the role of PAK teachers as facilitators in supporting students' spiritual and moral growth. The research method used is literature study and descriptive analysis. The research results show that the role of PAK teachers as facilitators involves the ability to accompany students in understanding God's word, directing meaningful discussions, and encouraging students to actively participate in learning. Additionally, this approach has proven effective in building spiritual awareness, increasing theological understanding, and strengthening students' relationship with God. However, this role also faces challenges, such as time constraints, lack of curriculum support, and variations in students' levels of understanding. Therefore, special training and competency development for PAK teachers is needed to maximize the role of facilitators in learning.